Improving Critical Thinking Skills OF High School Students Through Gamification-Based Learning Media Development - Ade Fitria; Dwiyono Hari Utomo; Tuti Mutia; Ahmad Nubli Gadeng (Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to develop gamification-based learning media and test the effectiveness of the media on students' critical thinking skills. This study uses the Research and Development methodology, the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this research trial were class X geography students at the Pasanggaran High School in East Java, which consisted of an experimental class and a control class. Sampling using a purposive sampling technique. The type of data used is quantitative data. Collecting data using questionnaires and tests using descriptive analysis techniques. The respondent's due diligence resulted in 8326 and has been validated. The results showed that the use of gamification-based learning media had a positive effect on students’ critical thinking skills using sig. 0.000 0.05. Thus, gamification-based learning media is feasible to use and influences students' critical thinking skills.